Ocrelizumab in pediatric multiple sclerosis - Bibinoğlu Amirov, Ceren; Saltık, Sema; Yalçınkaya, Cengiz; Tütüncü, Melih; Saip, Sabahattin; Siva, Aksel; Uygunoğlu, Uğur (European journal of paediatric neurology, 2023)
Ocrelizumab is a recombinant humanized anti-CD20 monoclonal IgG1, approved by FDA and EMA for adult patients with multiple sclerosis (MS). The data on the efficacy and safety of Ocrelizumab for pediatric MS cases are limited. Here, we describe pediatric relapsing-remitting MS (P-RRMS) cases who were treated with Ocrelizumab as a disease-modifying drug. P-RRMS cases who were started Ocrelizumab below 18 years-of-age and followed-up >12 months with Ocrelizumab treatment were included. The primary end-points were annualized relapse rate (ARR) and magnetic resonance imaging (MRI) activity (new/enlarging T2 lesions and new gadolinium (Gd) enhancing lesions). The secondary end-points were the percentage of patients who remain relapse-free and/or free from Gd enhancing lesions, Expanded Disability Status Scale (EDSS) score, and the safety profile of Ocrelizumab. Of 18 P-RRMS cases receiving Ocrelizumab, 10 patients fulfilled the inclusion criteria for our study. The median duration of follow-up under Ocrelizumab was 28,3 months (min: 15 months, max: 46 months). Mean ARR decreased from 2.01 (±0.71) to 0 during the follow-up of Ocrelizumab treatment (P < 0.0001). None of the patients had MRI activity during the treatment. Mean EDSS decreased from 1.75 (±1.09) to 1.20 (±0.63) from the initiation of Ocrelizumab to the last follow-up of the patients (P = 0.024). None of the patients had serious side effects, except one patient who experienced anaphylaxis. Ocrelizumab can be considered a safe and effective treatment option in highly active P-RRMS.